2016
DOI: 10.1016/j.envres.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Interactive and additive influences of Gender, BMI and Apolipoprotein 4 on cognition in children chronically exposed to high concentrations of PM2.5 and ozone. APOE 4 females are at highest risk in Mexico City

Abstract: Children's air pollution exposures are associated with systemic and brain inflammation and the early hallmarks of Alzheimer's disease (AD). The Apolipoprotein E (APOE) 4 allele is the most prevalent genetic risk for AD, with higher risk for women. We assessed whether gender, BMI, APOE and metabolic variables in healthy children with high exposures to ozone and fine particulate matter (PM2.5) influence cognition. The Wechsler Intelligence Scale for Children (WISC-R) was administered to 105 Mexico City children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 98 publications
4
37
0
Order By: Relevance
“…Although olfactory impairment, or anosmia, occurs during normal aging 95,96 , anosmia frequently precedes many neurological disorders [97][98][99][100][101] . Furthermore, studies have shown correlations with the levels of air pollution with olfactory impairment 34,102-105 and neurodegenerative disease pathology, such as Alzheimer's disease [106][107][108][109][110][111] , though the mechanism behind these correlations is unclear. Anosmia has many causes, such as smoking and head trauma 102 , and toxin exposure is another source of olfactory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Although olfactory impairment, or anosmia, occurs during normal aging 95,96 , anosmia frequently precedes many neurological disorders [97][98][99][100][101] . Furthermore, studies have shown correlations with the levels of air pollution with olfactory impairment 34,102-105 and neurodegenerative disease pathology, such as Alzheimer's disease [106][107][108][109][110][111] , though the mechanism behind these correlations is unclear. Anosmia has many causes, such as smoking and head trauma 102 , and toxin exposure is another source of olfactory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies explored effect modification by gender/sex as a supplementary purpose concerning examining the main effects of air pollution on cognitive function (11,20), the results were varied. Specifically, previous research found that the effect of air pollution exposure on cognition was different between males and females (21,22), while no such result was found for other research (23). Notably, there is a discrepancy over whether the effect is higher in males than females or vice versa (21)(22)(23).…”
Section: Introductionmentioning
confidence: 94%
“…Known influences include gender, body mass index (BMI), and presence of the APOE4 allele. [29] Epidemiological studies have examined the effects of O 3 on cognition. Long term O 3 exposure (14-years) is associated with increased risk for vascular dementia in the elderly.…”
Section: Air Pollution and Cognitive Dysfunctionmentioning
confidence: 99%